Balancing Audience’s Needs and Producer’s Expectations in Television Serial Drama Programming - Wagumba, Collins Auta; Kamau, Michael M (Jurnal Komunikasi Islam, 2020)
The study sheds light on how the TV station executives balance the entertainment needs of its audience and the producers' expectations within a changing digital broadcast environment. The study is anchored on uses and gratification and the encoding and decoding theories. The research employs a mixed-method design by using survey questionnaires (415), FGDs, and in-depth interviews with 5 TV station executives and serial drama fiction producers in Kenya. The results indicate that the station executive takes centre stage to fulfil the urban audience’s needs and the producers’ needs respectively. The station executives contextualize the viewers and the serial drama producers as “profit vessels” and any decision made towards them should culminate in economic benefit to the station